2009
DOI: 10.1590/s0036-36342009000100004
|View full text |Cite
|
Sign up to set email alerts
|

Social networks and health-related quality of life: a population based study among older adults

Abstract: Social networks and health-related quality of life: a population based study among older adults. Salud Publica Mex 2009;51:6-13. AbstractObjective. To examine the relationship between components of social networks and health-related quality of life (HRQL) in older adults with and without depressive symptoms. Material and Methods. Comparative cross-sectional study with data from the cohort study "Integral Study of Depression", carried out in Mexico City during 2004. The sample was selected through a multi-stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 35 publications
6
29
0
2
Order By: Relevance
“…The differences within this effect between men and women were particularly strong for instrumental and informational support, which suggests that women profit better from these types of support in terms of prevention of depressive symptoms. In one study, social support was reported to be related to lower depression even irrespective of gender [16]. However, our findings linking higher social support with lower depression in women whereas to a lesser degree in men are corroborated by findings from some other studies.…”
Section: Discussionsupporting
confidence: 89%
“…The differences within this effect between men and women were particularly strong for instrumental and informational support, which suggests that women profit better from these types of support in terms of prevention of depressive symptoms. In one study, social support was reported to be related to lower depression even irrespective of gender [16]. However, our findings linking higher social support with lower depression in women whereas to a lesser degree in men are corroborated by findings from some other studies.…”
Section: Discussionsupporting
confidence: 89%
“…Depression, anxiety and somatic symptoms have been associated with decreased QoL among various types of elder samples and in different settings/ countries [28][29][30][31][32]76], and in a recent study among older persons it was found that psychological well-being predicted QoL [126]. Thus, our findings seem to confirm those of a plethora of studies.…”
Section: Qol and Healthsupporting
confidence: 88%
“…To our knowledge, previous research of social relationships in México and in other developing countries has been focused on isolated aspects of social relationships [31,32]. Therefore, deriving social network typologies could provide valuable information to better understand the current social conditions of older adults.…”
Section: Discussionmentioning
confidence: 99%